STUDENTS’ SPEAKING SKILL OF PROCEDURE TEXT AT XI GRADE OF SOCIAL SCIENCES 2 OF SMAN 1 KAMPAR - Resi Rahmanis (Journal of English Language and Education, 2019)
This research aims to describe the students’ speaking skill of procedure text at grade XI IPS 2 SMAN 1 Kampar academic year 2016/2017. The subjects of this research were consisted 31 students. The method of this research is descriptive method. Based on the data analysis of the research showed that the average of the students’ achievement at the XI Grade IPS 2 in speaking skill is 51. It is categorise in weak level. Furthermore, the students’ speaking skill of procedure text at XI grade IPS 2 showed that 9 or 29% the students could learning speaking of procedure text. Meanwhile, 22 or 71% could not understand of speaking procedure text. It is supported the result of the students’ speaking skill of procedure text is still low.